Olfactory bulb acetylcholine release dishabituates odor responses and reinstates odor investigation - M. Cameron Ogg (Nature Portfolio, 2018)
Habituation reduces neural responsiveness to prolonged irrelevant stimuli and dishabituation reverses these effects when a salient stimulus is encountered. Here the authors demonstrate that acetylcholine is involved in dishabituating odor responses in the mouse olfactory bulb.